The Truman Administration and Bolivia : Making the World Safe for Liberal Constitutional Oligarchy - Dorn, Glenn J. (Book collections on Project MUSE., 2011)
"Examines the interaction of the Truman administration in U.S. and five Bolivian governments in years leading up to Victor Paz Estenssoro's National Revolution, focusing on negotiations over the price of tin"--Provided by publisher.